Long-term spatiotemporal distribution, abundance, and priority areas for manatees and calves (Trichechus manatus Sirenia: Trichechidae) in Guatemala. - Quintana-Rizzo, Ester; Machuca-Coronado, Oscar; Garcia, Heidy Amely (Revista de Biología Tropical)
Introduction: The Antillean manatee (Trichechus manatus manatus) is an endangered species found throughout the Caribbean, and the coastal waters of Central and northeastern South America. Their low numbers are the result of a variety of human-related pressures. A small population of manatees has been identified in Guatemala; however, their spatial and temporal dynamics remain unclear. Objective: To examine long-term trends in the spatiotemporal distribution and abundance of manatees in Guatemala. This included identification of priority areas for manatees including the presence of calves, assessing whether distribution areas are inside protected areas, and studying the relationship between manatee sightings and human activities. Methods: Nine years of standardized aerial surveys were conducted along the Atlantic coast (1992, 2005-2008, 2010-2011, 2014, 2022). Quantitative approaches to detect priority areas, specifically the Kernel density estimation and the Getis-Ord Gi* statistic, were used in the spatiotemporal analysis. A Spearman rank correlation analysis tested for significant correlations between human activities, coastline topographies, and manatee numbers along coastline segments. Manatee abundance across years, survey sections, and protected areas were also examined. Results: A total of 293 sightings and 518 manatees were observed including 476 adults (92 %) and 42 calves (8 %). Manatees were most frequently observed as solitary individuals (60 %). Most manatee (61 %) and calf (68 %) sightings occurred inside protected areas where several priority areas were identified. The two priority areas were Refugio de Vida Silvestre Bocas del Polochic (Bocas del Polochic) and Refugio de Vida Silvestre Punta de Manabique, which were identified as important manatee habitats in 1992. Bocas del Polochic had the highest manatee abundance of all protected areas (p < 0.05). However, a shift in manatee distribution was recorded in 2014, although the cause is unclear. No annual significant differences in manatee abundance were found over time (p = 1.0), but significant differences in abundance were detected between survey sections and protected areas (p < 0.05). Manatee numbers had positive significant correlations with ecological and human parameters. The highest correlation was between manatees and rivers (p < 0.01), and the weakest correlation was between manatees, motorboats, and fishing nets (p < 0.01). Conclusions: The results indicate that the local manatee population remained relatively stable for over 20 years, although changes in overall distribution were noted. It is unclear if the changes are temporary or permanent. As a sentinel species, manatee distribution shifts can be used as early warnings about the health of the environment and can depict current or potential impacts on individual- and population-level animal health.